(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article will talk about ensuring that teachers of mathematics and Informatics who are studying have excellent knowledge and skills by connecting specialist subjects that are suitable for their direction. Students in this direction learn to solve problems of different difficulty in mathematics, while in computer science they have information about positional number systems, in which they have the skills to perform different actions. Currently, excellent characteristic number systems have been developed along with traditionalist position number systems. Such number systems help to easily solve problems of various difficulties related to mathematics and computer science. In this direction, the article presents ideas aimed at improving students ’ academic skills and practical qualifications and enhancing their interest in the sciences. At the same time, it is indicated to perform some practical tasks.